White opaque substance visualized by magnifying narrow-band imaging is associated with intragastric acid conditions - Togo, Kazumi; Ueo, Tetsuya; Yao, Kenshi; Wada, Kurato; Honda, Hideho; Inoue, Syotaro; Fukuda, Masahide; Yanai, Yuka; Yonemasu, Hirotoshi; Murakami, Kazunari (Endoscopy International Open, 2018)
Background and study aims The presence of white opaque substance (WOS) is an endoscopic marker of intestinal metaplasia. Considering that the nature of WOS is absorbed lipid droplets, lipase plays an important role in the lipid absorption process and is inactivated at strong acidity. WOS may only be present in a hypochlorhydria state following Helicobacter pylori infection, and, thus, may not be highly sensitive marker, especially in H. pylori-eradicated patients. We investigated the relationship between WOS and gastric acid conditions.Patients and methods A total of 501 patients were retrospectively evaluated for the presence of WOS at 2 regions of interest using magnifying narrow-band imaging. The pH level of collected gastric juice was also measured. Study end points were (1) prevalence of WOS and its relationship with gastric juice pH in 3 groups: H. pylori-uninfected, H. pylori-infected, and H. pylori-eradicated; (2) the relationship between prevalence of WOS and gastric juice pH before and after proton pump inhibitor (PPI) administration in 29 H. pylori-eradicated cases.Results Prevalence of WOS was 0 % (0 /206), 28.4 % (31/109), and 3.2 % (6/186) in the H. pylori-uninfected, H. pylori-infected, and H. pylori-eradicated groups, respectively. Mean gastric juice pH was significantly higher in WOS-positive cases than in WOS-negative cases in the H. pylori-infected and H. pylori-eradicated groups (P < 0.0001). Mean gastric juice pH increased from 1.1 to 6.9 after PPI administration and WOS prevalence increased from 0 % (0/29) to 45 % (13/29) of cases.Conclusion The prevalence of WOS is closely associated with the neutralization of intragastric pH.